ПОРІВНЯННЯ МЕТРОЛОГІЧНИХ ВЛАСТИВОСТЕЙ СХЕМ ЦИФРОВИХ ПЕРЕТВОРЮВАЧІВ ДЛЯ РЕЗИСТИВНИХ ТЕРМОСЕНСОРІВ - Латенко, В.І.; Орнатський, І.А.; Філь, С.О.; Зайцев, Є.О. (Інститут електродинаміки НАН України, Київ, 2021)
In this paper presents comparative metrological analysis of two options for connecting Pt100 resistive temperature sensors to high-precision analog-to-digital converters is carried out: a proportional circuit in which the reference resistor serves to form the reference voltage, and a canonical 4-wire circuit where the resistance of the reference resistor is measured in the same way as the resistance of the temperature sensor are presented. It is shown that the error of the one-stroke proportional circuit is determined by the long-term instability of the gain, while the resulting error of the push-pull canonical circuit is determined by the short-term instability of several elements. The insignificant advantage of the canonical circuit with the accuracy of conversion and in the absence of additional requirements for the input of the reference voltage is affirmed, which gives recommendations for the practical application of the circuits considered in meters of temperature. References 10, figures 2, table 1.